Introduction [in Achieving a nutrition revolution for Africa: The road to healthier diets and optimal nutrition] - Covic, Namukolo; Hendriks, Sheryl L. (International Food Policy Research Institute, 2016)
Focusing the 2015 Annual Trends and Outlook Report (ATOR) on nutrition will contribute to a broader understanding of the role and importance of nutrition in achieving international, continental, and national economic growth targets through agriculture, food security, and nutrition. This report presents information and analysis in support of evidencebased policy making at the moment when the second-generation CAADP national investment plans are being developed. This is an important moment for shaping the region’s future and ensuring that the much-needed agriculture-led growth and development agenda can simultaneously deliver on improving nutrition and health, saving lives, improving the productivity of Africa’s population, and curbing public health expenditure on nutrition-related diseases. This includes addressing not only the usual elements of undernutrition but also widespread micronutrient deficiencies (termed “hidden hunger”) and the growing problem of overweight and obesity that is increasing across the African continent.